The Shield of Perseus. War and Peace in a Reading about Norberto Bobbio (2005)
War and peace is one of the central themes of the intellectual work of Norberto Bobbio. The article exposes the basic ideas of the Italian philosopher on this subject, following three basic clues of his research method: conceptual elaboration, methodologi